Efek Ekstrak Kulit Manggis Terhadap Gambaran Histopatologi Hepar Tikus Wistar Yang Diinduksi Formalin - Rohmani, Afiana; Rakhmawatie, Maya Dian (Universitas Muhammadiyah Semarang, 2015)
Effects of Mangosteen Peel Extract on Histopathological Appearance of Wistar Rats Induced by FormalinBackground: Formalin chemical idamage can stimulate the formation of reactive oxygen species (ROS) compounds that can cause cellular damage to the body. Mangosteen rind is known as a natural antioxidant due to its xanton content.Objective: To determine the effect of mangosteen peel extract on liver histopathology in Wistar rats induced by formalin solution.Methods: 24 rats were divided into 4 groups. The first group is a negative control group (K-), only given a placebo until the termination period. The second group was a positive control group (K+) which was induced by oral formalin for 21 days, then was given a placebo for 7 days. The third group as Treatment group 1 (P1) were induced by oral formalin for 21 days and then given mangosteen peel extract 200mg/kg BW/day for 7 days. The fourth group as Treatment group 2 (P2) were induced by oral formalin for 21 days and then given mangosteen peel extract 400mg/kg BW/day for 7 days. After that, the rats were terminated and their livers were taken to make histopathological preparations.Results: There was a significant difference (p=0.008) in the histopathological picture of liver tissue in the group of rats given mangosteen peel extract 400mg/kg BW/day (P2) and the positive control group (P2). K+). There was no significant difference (p=0.715) in the histopathological picture of liver tissue in the group of rats given mangosteen peel extract 200mg/kg BW/day (P1) and the positive control group (K+). There was a significant difference (0.00) in the histopathological picture of the liver tissue of the negative control group (K-) with the three groups that were induced by formalin, either given mangosteen peel extract (P1 and P2) or not (K+). Latar Belakang : Jejas kimia formalin dapat memacu terbentuknya senyawa reactive oxygen species (ROS) yang dapat menyebabkan kerusakan seluler jtubuh. Kulit manggis dikenal sebagai antioksidan alamiah dari kandungan xanton di dalamnya. Tujuan: mengetahui efek pemberian ekstrak kulit manggis terhadap gambaran histopatologi hepar pada tikus wistar yang diinduksi larutan formalin. Metode Penelitian: 24 ekor tikus dibagi menjadi 4 kelompok . Kelompok pertama merupakan kelompok kontrol negatif (K-), hanya diberi placebo saja hingga masa terminasi. Kelompok kedua merupakan kelompok kontrol positif (K+) yang diinduksi formalin peroral selama 21 hari, kemudian diberi placebo selama 7 hari. Kelompok ketiga sebagai kelompok Perlakuan 1 (P1) yang diinduksi formalin peroral selama 21 hari kemudian diberi ekstrak kulit manggis 200mg/kg BB/hari selama 7 hari. Kelompok keempat sebagai kelompok Perlakuan 2 (P2) yang diinduksi formalin peroral selama 21 hari kemudian diberi ekstrak kulit manggis 400mg/kg BB/hari selama 7 hari. Setelah itu tikus diterminasi dan diambil organ heparnya untuk dibuat preparat histopatologi. Hasil: Terdapat perbedaan yang signifikan (p=0,008) gambaran histopatologi jaringan hepar pada kelompok tikus yang diberi ekstrak kulit manggis 400mg/kg BB/hari (P2) dengan kelompok kontrol positif (K+). Tidak terdapat perbedaanyang signifikan (p=0,715) gambaran histopatologi jaringan hepar pada kelompok tikus yang diberi ekstrak kulit manggis 200mg/kg BB/hari (P1) dengan kelompok kontrol positif (K+). Terdapat perbedaan yang signifikan (0,00) gambaran histopatologi jaringan hepar kelompok kontrol negatif (K-) dengan ketiga kelompok yang diinduksi formalin, baik diberi ekstrak kulit manggis (P1 dan P2) maupun yang tidak (K+)